A companion to Eastern European cinemas - Shaviro, Steven (Wiley-Blackwell companions to national cinemas., 2012)
A Companion to Eastern European Cinemas showcases twenty-five essays written by established and emerging film scholars that trace the history of Eastern European cinemas and offer an up-to-date assessment of post-socialist film cultures.